Pengaruh Pola Asuh Ibu Terhadap Kemandirian Anak Usia 5-6 Tahun di TK PGRI 5 Mataram - Triana Nadya Salsabilla; Gunawan Gunawan; Baik Nilawati Astini; Ika Rachmayani (Indonesian Journal of Elementary and Childhood Education, 2023)
This study aims to determine the Influence of Mother Parenting Styles on the Independence of Children Aged 5-6 Years at  PGRI Kindergarten 5 of Mataram. The number of samples is 38, and the type of research used is a survey study utilizing a close-ended questionnaire and employing a Likert scale. The sample was selected using purposive sampling technique, consisting of 38 individuals. The data collection method involved distributing questionnaires. The data analysis method used in this study is descriptive statistical analysis. The results of the normality test showed a value of 0,200.The significance value is greater than 0,05, which leads to the conclusion that the residual values are normally distributed. It is observed that working mothers tend to apply the democratic parenting style, with the highest score of 2,905. A significant difference is seen in the authoritarian parenting style, where housewives reach a score of 2,867. Additionally, a quite striking difference is observed in the permissive parenting style, where working mothers show a higher score of 2,856 compared to housewives, who score 2,670. These differences may reflect the distinct roles and environments faced by working mothers and housewives. The significance value obtained from the software is less than 0,05, indicating that the maternal parenting style variable (X) significantly influences the child independence variable (Y). Meanwhile, based on the comparison of the t-test value and the t-table value, the t-test value is greater than the t-table value, which is 7,417 > 2,02809. Based on this, it can be concluded that there is an influence of the maternal parenting style (X) on the independence of children (Y) aged 5-6 years at PGRI Kindergarten 5 of Mataram.